Cross-Religious Political Communication: Christian Candidates and Muslim Voters in Papua’s 2024 Election - Abdul Qadir Abdul Qadir; Imam Alfian Kadir (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study analyzes the political communication strategy in the 2024 Papua Gubernatorial Election, focusing on the cross-religious approach employed by the Benhur Tomi Mano (BTM) and Yeremias Bisai pair. Specifically, this research examines how a Christian candidate navigates political marketing within a Muslim-minority context through the "Krimuha" (Christian-Muhammadiyah) branding. Using a qualitative descriptive method, data were collected through in-depth interviews and social media analysis (Instagram, TikTok, and Facebook). The study utilizes Political Marketing Theory and Identity Negotiation Theory to dissect campaign narratives. The results indicate that the BTM-Yeremias pair successfully implemented a segmentation strategy by blending nationalist figures with religious inclusivity. The effectiveness of this strategy lies in the "persona management" on social media, which framed the candidate not only as a former bureaucrat but as a figure accepted by Islamic grassroots (Muhammadiyah/NU). This research concludes that in conflict-prone areas like Papua, political communication that highlights intercultural harmony is more effective than rigid identity politics.